Validity of Hematological scoring system in diagnosis of neonatal sepsis at Birat Medical College Teaching Hospital - Bhattarai, Soorya; Singh, Mrinalini; Sedhain, Sapana; Kafle, Neeta; Sinha, Amrita (Birat Journal of Health Sciences, 2024)
Introduction: Newborns are vulnerable to infections. Timely diagnosis of neonatal sepsis can avoid major morbidity and mortality. Neonates with sepsis present with non-specific signs and symptoms. Timely diagnosis is important. Though blood culture is gold standard, it consumes time. Hematological scoring system (HSS) using hematological parameters can be effective in early diagnosis of sepsis.Objectives: To evaluate the effectiveness (Sensitivity, specificity, Positive Predictive value (PPV), Negative Predictive value (NPV) of HSS and their individual parameters in diagnosis of neonatal sepsis.Methodology: This was the cross-sectional study done at tertiary care hospital for period of six months. Neonates with clinical suspicion of sepsis were included in the study. Blood was drawn from neonate in two vials, one was sent for culture and other for calculation of hematological parameters as per Rodwell Hematological scoring system. Diagnostic study parameters were calculated.Result: Total of 143 neonates clinically suspected of sepsis were included in the study with 83 having positive blood culture. Highest sensitivity (86.7%) was recorded for Total Polymorph neutrophil (PMN) while highest specificity (93.3) and PPV (81.8) for I: T PMN ratio. A sensitivity of 67.5% and specificity of 91.7% was seen along with PPV of 91.8% and NPV of 67.1% with HSS greater than or equal to 5.Conclusion: HSS of greater than or equal to 5 can be considered to be the reliable screening tool for diagnosis of sepsis.